Concerto for guitar and orchestra by Heitor Villa-Lobos: genre and style projections - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the article is to consider Guitar Concerto by Heitor Villa-Lobos is considered from the standpoint of the interaction of authentic Brazilian genres with the specifics of the individual composer’s style. The article takes into account historiographical information, as well as editorial and performing aspects of comparative analytics by contemporary researchers. Main objective of the study is to identify genre sources of thematicism, linguistic features of Brazilian origin in the Guitar Concerto by Heitor Villa-Lobos in combination with individual and stylistic means of their modern embodiment. The novelty of the publication lies in the introduction of genre and style analytics of H. Villa-Lobos’s Guitar Concerto into Ukrainian musicology, taking into account the specific direction of modernist searches for musical vocabulary, tangentially related to the renewal of the instrument’s idiomatic resources and performance techniques, explanations of the structural logic of pitch phenomena, as well as the expansion of the range of manifestations of the phenomenon of autocitation. The methodology is based on an interdisciplinary approach and methods of historical-theoretical, systemic, structural and functional analysis used to study the rhythmic and intonational primary sources of authentic Brazilian genres, stylistic features of the composer’s work, folk and academic guitar performance techniques, and the relationship between the morphology of modernist thinking and the idiom of new guitar playing techniques. Results and conclusions. The Concerto reveals genre primary sources of thematicism, linguistic features of Brazilian origin in combination with individual and stylistic means of their modern embodiment. The phenomenon of autocitation is identified as one of the main creative methods of the author’s declaration of accumulations and achievements in guitar music. Due to the leading influence of the Brazilian genre traditions of choro, the Concerto contains allusions related to the texts of the author’s own guitar cycles of preludes, choros, and etudes. The novelty of the study also lies in the analytically proven connection between the themes of the concerto and the musical material of Choro’s famous piano piece No. 5 «Alma Brasileira» from the cycle «Choros», created by the composer for different instruments and compositions. The use of the national attribution of Spanish hemiolaic modes as an element of Iberian culture is merged with the modes of octatonic symmetrical harmonies. In the aggregate of techniques, performance methods, melodic, harmonic, rhythmic elements of the language, genre and style projections of Heitor Villa-Lobos’ music deep into national sound mythologies are accumulated.